If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 40 = 6p Reorder the terms: 40 + p = 6p Solving 40 + p = 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 40 + p + -6p = 6p + -6p Combine like terms: p + -6p = -5p 40 + -5p = 6p + -6p Combine like terms: 6p + -6p = 0 40 + -5p = 0 Add '-40' to each side of the equation. 40 + -40 + -5p = 0 + -40 Combine like terms: 40 + -40 = 0 0 + -5p = 0 + -40 -5p = 0 + -40 Combine like terms: 0 + -40 = -40 -5p = -40 Divide each side by '-5'. p = 8 Simplifying p = 8
| 5(n+2)-3(3n-5)=12 | | 5x^2-54=3x | | 9B=B+24 | | 11g+h=-5 | | 4.22-0.14x=5x-2.205 | | -7x+3(x+4)=8 | | 23/9*3 | | -24+2m=-22 | | 7k^2-20=-10k | | 14/18=42/? | | -2(v-2)=-4v-4 | | 12+24=-36t | | 8m-5+2m= | | 7/9=c/18 | | 4n^2+3=-5 | | 2y+6+3y=-7+2 | | (X-4.95)/x | | 17/5*4 | | X^2-3Z=5 | | -6w+4(w-8)=-12 | | 4n^2-13=-9 | | (2+4p)(5)= | | 7y=4y+30 | | (3v)-(12)=15 | | 5y+8x+5=180 | | 4x^2-11=47 | | X^2+5x^2=53 | | 2/5=10/6 | | 8cos^3x-4cosx-4cos^2x+1=0 | | 2(4-4x)+1=2(1x+2)-5x | | 3c=126 | | e^3x+5=e^6 |